1989
DOI: 10.1016/0009-2614(89)87526-8
|View full text |Cite
|
Sign up to set email alerts
|

Transient optical absorption spectroscopy of the photochemical spiropyran-merocyanine conversion

Abstract: The photochemical ring-opening reaction of 1',3',3'-trimethylspir~[2H-l-benzopyran-2,2'-indoline] has been followed by transient absorption spectroscopy, covering the range 370-650 nm with a temporal resolution of 0.42 ps. During the pump pulse, induced transient absorption is observed only at wavelengths shorter than 500 nm, with a maximum near 440 nm. The absorption at 440 nm decays within K 5 ps, while a broad absorption band appears at 550 nm in the region characteristic of merocyanine absorption. The rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 18 publications
3
47
0
1
Order By: Relevance
“…• The parameters £? and O)k are tuned to be optimal for the respective individual transition (38) implying three pump pulses and one dump pulse. Thus, the series of K=4 laser pulse sshould induce the sequence of one-photon vibrational transitions i.e., the reaction leads, from the ground state of the reactant isomer to the third excited state of the product isomer .…”
Section: Ek(t) =Ez Cos[k]sk(t-t K)mentioning
confidence: 99%
“…• The parameters £? and O)k are tuned to be optimal for the respective individual transition (38) implying three pump pulses and one dump pulse. Thus, the series of K=4 laser pulse sshould induce the sequence of one-photon vibrational transitions i.e., the reaction leads, from the ground state of the reactant isomer to the third excited state of the product isomer .…”
Section: Ek(t) =Ez Cos[k]sk(t-t K)mentioning
confidence: 99%
“…However, the time scale for the ring-opening reaction remains a debated point. In the early 90's, Ernsting and coworkers reported the results of optical pump-probe experiments in the visible range carried out on BIPS solutions in n-pentane 16,17 as well as ethanol 18 and observed the formation of merocyanine species upon excitation at 308 nm with a rise time of B0.9 ps. They found that the spectrum in the 450-600 nm range at 30 ps resembled that of one recorded in the microsecond timescales suggesting that the product is well-established within this time frame.…”
Section: Introductionmentioning
confidence: 99%
“…3(b). Neither the yield nor the identity of this species have been elucidated, although it is unlikely to be a spiropyran formed by rearrangement of the cisisomer (Ernsting, 1989), and will be addressed in a later study employing time-resolved resonance Raman detection facilities. The absence of any apparent 02-quenching effect implies that this tranwavelength/ nm Figure 4.…”
Section: -mentioning
confidence: 99%